Find the value of k which minimizes ∫ 0 4 ∣ x ( 4 − x ) − k ∣ d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Ugh, I had the idea of substituting x to simplify the computations but instead of 2-u I substituted for u-2. I quickly dropped the idea and brute forced the solution out.
We are going to use the following formula without proof. Searching "Leibniz integral rule" will let you find a proof of this result online.
Let I ( α ) = ∫ a ( α ) b ( α ) f ( x , α ) d x .
Then
d α d I = f ( b , α ) d α d b − f ( a , α ) d α d a + ∫ a ( α ) b ( α ) ∂ α ∂ f ( x , α ) d x .
Furthermore, it is clear that the required value of k is between 0 and 4 (this can be seen graphically).
For 0 ≤ k ≤ 4 , the line y = k intersects the parabola y = x ( 4 − x ) at x = 2 ± 4 − k . Between these two roots, the parabola is above the line - and thus x ( 4 − x ) − k ≥ 0 , and elsewhere in [ 0 , 4 ] we have x ( 4 − x ) − k ≤ 0 . Thus,
F ( k ) = ∫ 2 − 4 − k 2 + 4 − k ( x ( 4 − x ) − k ) d x + ∫ 0 2 − 4 − k ( k − x ( 4 − x ) ) d x + ∫ 2 + 4 − k 4 ( k − x ( 4 − x ) ) d x .
Using the above result,
d k d F = − ∫ 2 − 4 − k 2 + 4 − k d x + ∫ 0 2 − 4 − k d x + ∫ 2 + 4 − k 4 d x .
Setting this equal to 0 ,
4 = 4 4 − k so k = 3
thank you for the solution but shouldn't the upper limit of the second integral part in F(k) be 2 − 4 − k ?
Log in to reply
Yep - sorry about that! I've now corrected it.
Problem Loading...
Note Loading...
Set Loading...
I ( k ) = ∫ 0 4 ∣ x ( 4 − x ) − k ∣ d x = ∫ − 2 2 ∣ ( 2 − u ) ( 2 + u ) − k ∣ d u = 2 ∫ 0 2 ∣ 4 − k − u 2 ∣ d u Let u = 2 − x ⟹ d u = − d x Since the integrand is an even function
For k ≤ 0 ,
I ( k ≤ 0 ) = 2 ∫ 0 2 ( 4 − k − u 2 ) d u = 2 [ 4 u − k u − 3 u 3 ] 0 2 = 3 3 2 − 4 k
⟹ min ( I ( k ≤ 0 ) ) = 3 3 2 , when k = 0 .
For 0 < k < 4 ,
I ( 0 < k < 4 ) = 2 ∫ 0 2 ( 4 − k − u 2 ) d u = 2 ∫ 0 4 − k ( 4 − k − u 2 ) d u + 2 ∫ 4 − k 2 ( u 2 − 4 + k ) d u = 3 8 ( 4 − k ) 2 3 + 3 1 6 − 4 ( 4 − k )
To find min ( I ( 0 < k < 4 ) ) , d k d I ( k ) = − 4 4 − k + 4 . Putting d k d I ( k ) = 0 , ⟹ 4 − k = 1 ⟹ k = 3 . Therefore min ( I ( 0 < k < 4 ) ) = I ( 3 ) = 4 .
For k ≥ 4 ,
I ( k ≥ 4 ) = 2 ∫ 0 2 ( u 2 − 4 + k ) d u = 2 [ 3 u 3 − 4 u + k u ] 0 2 = 4 k − 3 3 2
⟹ min ( I ( k ≥ 4 ) ) = 3 1 6 .
Therefore min ( I ( k ) ) = 4 , when k = 3 .